2019
DOI: 10.3389/fmicb.2019.02362
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Virulence-Related Traits in Pseudomonas syringae pv. actinidiae by Gunpowder Green Tea Extracts

Abstract: Green tea is a widely-consumed healthy drink produced from the leaves of Camellia sinensis. It is renowned for its antioxidant and anticarcinogenic properties, but also displays significant antimicrobial activity against numerous human pathogens. Here we analyzed the antimicrobial activity of Gunpowder green tea against Pseudomonas syringae pv. actinidiae (Psa), the agent that causes kiwifruit bacterial canker. At the phenotypic level, tea extracts strongly inhibited Psa growth and swimming motility, suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 86 publications
(106 reference statements)
1
16
1
Order By: Relevance
“…A single study was found in literature that reports the activity of green tea extracts in Pseudomonas syringae pv. actinidiae (Psa), the agent that causes kiwifruit bacterial cancer [ 76 ]. The results showed that tea extracts strongly inhibited Psa growth and swimming motility.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…A single study was found in literature that reports the activity of green tea extracts in Pseudomonas syringae pv. actinidiae (Psa), the agent that causes kiwifruit bacterial cancer [ 76 ]. The results showed that tea extracts strongly inhibited Psa growth and swimming motility.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…As with the other tested strains, the inhibitory concentration was lower than the reported at 1 mg/ml from prior studies (Lovato et al, 2019). These are promising results since it has been reported that in vivo conditions may vary from in vitro results; in particular, it has been reported EGCG extracts yield moderate to no inhibition in vivo assays (Lovato et al, 2019;Yang and Zhang, 2019).…”
Section: Evaluation Of Virulence In Tomato Plantssupporting
confidence: 62%
“…The mechanical application of EGCG-TuMV may have increased the number of superficial wounds that P. syringae can use for plant infection. EGCG treatment before inoculation (Fukai, Ishigami and Hara, 1991;Lovato et al, 2019) has been studied with adverse effects on plant virulence, which suggests that it is possible to approach treatment at this time. Further studies have to be done to determine if EGCG-TuMV treatment prior inoculation can be achieved by other application techniques without increasing virulence.…”
Section: Evaluation Of Virulence In Tomato Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial motility was measured using a swimming assay according to the method of Lovato [ 29 ]. Psa was incubated to OD 600 values of 0.6–0.8.…”
Section: Methodsmentioning
confidence: 99%